Correlational Study on the Use of Translation Technology and Translation Skills Among EFL Students - Reftyawati, Dian (Lexeme : Journal of Linguistics and Applied Linguistics, 2024)
This study investigated the correlation between the use of translation technology and the translation skills of students in the English Education Study Program at UIN Raden Intan Lampung. Employing a quantitative correlational research design, the research focused on a sample of 40 students from a Translation and Interpretation course. Data collection involved a translation test to assess students' proficiency and a questionnaire to measure the frequency and reliance on translation tools. Analysis using SPSS revealed a moderate positive correlation of 0.35 between the use of translation technology and translation skills, indicating that while technology aids in improving translation performance, it is not the only factor influencing students' abilities. Other elements, such as individual learning strategies and language proficiency, also play critical roles. The findings suggest that although translation tools are beneficial in language learning, they should be used in conjunction with traditional methods to prevent over-reliance. Educators are encouraged to promote manual translation exercises to foster deeper comprehension and skill development. However, the study's limitations, including its small sample size and focus on a single institution, may limit the generalizability of the results. Future research should consider larger, more diverse samples and explore the long-term effects of translation technology on student proficiency, offering broader insights into its impact on language education.